The structural basis for the modulation of protein function by protein phosphorylation - Johnson, Louise N. (Henry Stewart Talks, 2010)
Physical-chemical basis for phosphorylation, Discovery, Glycogen phosphorylase, Signaling from adrenaline to phosphorylase, Phosphorylase kinase still a challenge, Regulation of the cell cycle by phosphorylation, Cyclin dependent protein kinase 2 activation and inhibition, Rb the guardian of the genome, Control by p27 and cyclin E, Summary of the structural consequences of phosphorylation